Comparative Transcriptomics Reveals Discrete Survival Responses of S. aureus and S. epidermidis to Sapienic Acid - Moran, Josephine C.; Alorabi, Jamal A.; Horsburgh, Malcolm J. (Frontiers in Microbiology, 2017)
Staphylococcal colonization of human skin is ubiquitous, with particular species more frequent at different body sites. Whereas Staphylococcus epidermidis can be isolated from the skin of every individual tested, Staphylococcus aureus is isolated from < 5 % of healthy individuals. The factors that drive staphylococcal speciation and niche selection on skin are incompletely defined. Here we show that S. aureus is inhibited to a greater extent than S. epidermidis by the sebaceous lipid sapienic acid, supporting a role for this skin antimicrobial in selection of skin staphylococci. We used RNA-Seq and comparative transcriptomics to identify the sapienic acid survival responses of S. aureus and S. epidermidis. Consistent with the membrane depolarization mode of action of sapienic acid, both species shared a common transcriptional response to counteract disruption of metabolism and transport. The species differed in their regulation of SaeRS and VraRS regulons. While S. aureus upregulated urease operon transcription, S. epidermidis upregulated arginine deiminase, the oxygen-responsive NreABC nitrogen regulation system and the nitrate and nitrite reduction pathways. The role of S. aureus ACME and chromosomal arginine deiminase pathways in sapienic acid resistance was determined through mutational studies. We speculate that ammonia production could contribute to sapienic acid resistance in staphylococci.